PUSHOVER STUDY ANALYSIS OF PGRI FACULTY OF ENGINEERING BUILDING - Kurniati, Dwi; Bali Loko, Pelipus (University of Technology Yogyakarta, 2020)
The Faculty of Engineering Faculty of Engineering Building of PGRI Yogyakarta (UPY) is planning to be on medium ground, with a height of 7 floors functioned as a lecture hall.This building needs to be simulated the thrust of the earthquake load, in order to know the performance of the building.The purpose of this research is to want to know the performance value of poit direction x and direction y and performance level based on ATC 40 from upy engineering faculty building.Research method with the help of Etabs v16 software, in accordance with the guidelines of the National Standardization Agency namely SNI 1726-2012 and SNI 2847-2013.The results of the study obtained a peformance point value for push x 0.004 of 0.004 and push y of 0.003.As well as the level of performance is Immediate Occupancy (IO) which can be interpreted that in the event of an earthquake the structure is able to withstand an earthquake, the building does not suffer structural and non structural damage so that the building can be directly reused.